RANCANG BANGUN SISTEM TEMPERATUR DAN MONITORING TIMER PADA AUTOCLAVE BERBASIS MIKROKONTROLLER ATMega 8535 - Santa Lusi Sitohang; Fitria Priyulida (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2018)
Autoclave is heating tool and is used to sterilize things by using high pressure and high temperature steam 121C for about 15 minutes. The purpose of this tool is to kill endospores, resistant cell produced by bacteria. This cell is resistant against heat, dehydration and antibiotic. Research has been done for the design of time controlling and monitoring system at Autoclave based on microcontroller ATMega 8535. The purpose of this research is to produce Autoclave equipped with temperature controller and time monitoring which is beneficial to save energy and time using Autoclave. This tool is also equipped with circuit to detect problem. In this research, the tool’s operational system has been programmed with Thormocouple sensory system, Water Level, so the user can decide the temperature and time to be processed next by microcontroller. The initial Autoclave has been equipped with buzzer used as an alarm when the tool is not closed well and when the tool has finished operating